2016
DOI: 10.1016/j.molcel.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The S/T-Rich Motif in the DNAJB6 Chaperone Delays Polyglutamine Aggregation and the Onset of Disease in a Mouse Model

Abstract: Expanded CAG repeats lead to debilitating neurodegenerative disorders characterized by aggregation of proteins with expanded polyglutamine (polyQ) tracts. The mechanism of aggregation involves primary and secondary nucleation steps. We show how a noncanonical member of the DNAJ-chaperone family, DNAJB6, inhibits the conversion of soluble polyQ peptides into amyloid fibrils, in particular by suppressing primary nucleation. This inhibition is mediated by a serine/threonine-rich region that provides an array of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
215
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(272 citation statements)
references
References 57 publications
33
215
2
6
Order By: Relevance
“…In contrast, previous reports mostly focused on the functional study of DNAJB6(S) in neurodegenerative disease and LGMD1D (8, 10, 11), while the function of DNAJB6B(L) was less investigated (12, 13). Our present study further suggested that DNAJB6(L) , but not DNAJB6(S) , might function as an ER stress inhibitor.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, previous reports mostly focused on the functional study of DNAJB6(S) in neurodegenerative disease and LGMD1D (8, 10, 11), while the function of DNAJB6B(L) was less investigated (12, 13). Our present study further suggested that DNAJB6(L) , but not DNAJB6(S) , might function as an ER stress inhibitor.…”
Section: Discussionmentioning
confidence: 96%
“…While the first 6 exons encode the short cytoplasmic DNAJB6(S), the inclusion of the additional 2 exons at the 3′-end of the cDNA encodes the long nucleic DNAJB6(L). Mutations in DNAJB6(S) were reported to cause limb-girdle muscular dystrophy type 1D (LGMD1D), and DNAJB6(S) has been proposed to ameliorate protein aggregation–induced cytotoxicity in neurodegenerative diseases via its antiaggregation function (10, 11). In contrast to the more widely studied DNAJB6(S), functions of DNAJB6(L) remains less investigated (12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous small-molecule compounds have been described that activate cellular stress response pathways and reduce the aggregation of disease proteins or enhance their clearance by increasing chaperone levels (13,(179)(180)(181). A key role in aggregation prevention and aggregate dissociation is played by the Hsp70 machinery, as shown by overexpressing single or multiple components of the system in cellular and animal disease models (124,154,182,183). Finally, activating the UPS or inducing autophagy with smallmolecule compounds can enhance degradation and reduce aggregate load (184,185).…”
Section: Research | Reviewmentioning
confidence: 99%
“…Both bind stretches of glutamine (polyQ) in a number of different proteins, suppressing their aggregation [11]. A serine/threonine (S/T) rich region within these proteins is crucial for this binding ability [12, 13]. This is a particularly relevant example, as aggregation of proteins having polyQ stretches is responsible for a number of neurological disorders, including Huntington’s disease [14].…”
Section: Getting Substrate Protein and Hsp70 Togethermentioning
confidence: 99%